Fano resonance between coherent acoustic phonon oscillations and electronic states near the bandgap of photoexcited GaAs. Issue 1 (December 2018) - Vinod, M.; Raghavan, G.; Sivasubramanian, V.
Abstract Impulsive photo-excitation of solids results in a travelling strain pulse which manifests itself as coherent acoustic phonon oscillations. These oscillations have been extensively studied using time-resolved pump-probe spectroscopy. In the present work, we report the generation of extremely long-lived, coherent longitudinal acoustic phonon oscillations in intrinsic GaAs (100), with clear and unambiguous evidence of Fano interference between these oscillations and the continuum of electronic states close to the bandgap. Fano resonance is a widespread phenomenon observed in atomic systems and condensed media that arises from quantum interference between a continuum of quantum states and a discrete quantum state. Among other techniques, Fano resonance has been investigated with respect to optical phonons studied with Raman Spectroscopy. In the present work, we investigate Fano resonance in coherent phonon oscillations generated without the aid of any capping layer, dopants or substrate/interface effects. Since Fano resonance is sensitive to changes in electronic structure, doping and defects, these observations are important to the field of picosecond ultrasonics which is used for non-destructive depth profiling of solids and for carrier diffusion studies.